Osteoma - Faiz Alwan Moharry; Indra Zachreini (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Osteoma is a benign osteoblastic mesenchymal tumor consisting of differentiated mature bone tissue. Ear canal osteoma is an osteoma that occurs in the external acoustic canal. Osteoma of the ear canal is usually asymptomatic, but several symptoms that can accompany a total occlusion of the external acoustic canal are vertigo, tinnitus, which can also cause recurrent otitis externa, otorrhoea and otalgia. Mr. S came to the ENT Poly at Cut Meutia Hospital with complaints that his left ear felt blocked since 1 year ago. hearing loss in left ear. Left ear often bleeds when prying. Sometimes the patient feels pain in the left ear, and a clear, odorless discharge comes out of the left ear. The patient's left ear is often buzzing. On examination the local physical status found a solid mass, immobile, stalked, and unilateral and had closed all of the left external auditory canal. The tuning test found conductive deafness in the left ear. The patient was planned for CT-Scan Mastoid and osteoma excision surgery.